The disruption of human trophoblast functions by autophagy activation through PI3K/AKT/mTOR pathway induced by exposure to titanium carbide (Ti3C2) MXene. (July 2022) - Yang, Limei; Hu, Le; Tang, Hongyu; Chen, Xuemei; Liu, Xueqing; Zhang, Yue; Wen, Yixian; Yang, Yongxiu; Geng, Yanqing
Abstract: Ti3 C2 MXene, as a novel nanomaterial, has attracted great attention due to its promising properties in biomedical applications. However, the potential effects of Ti3 C2 MXene on trophoblast functions have not been investigated. Here, we found that Ti3 C2 MXene exposure weakened the extension ability of villus explants in vitro . We employed human trophoblast HTR-8/SVneo cells to reveal the underlying molecular mechanisms by which Ti3 C2 MXene exposure affected trophoblast functions. Results showed that Ti3 C2 MXene entered cells and mostly deposited in the cytoplasm, inhibiting cell migration and invasion abilities. Furthermore, we found that Ti3 C2 MXene exposure elevated autophagy through the inhibition of the PI3K/AKT/mTOR pathway. Meanwhile, the application of an autophagy inhibitor (3-MA) prevented autophagy and restored cell viability, resulting in the recovery of cell migration and invasion abilities. These indicated that the cellular dysfunction induced by Ti3 C2 MXene may be mediated by autophagy activation. Our results indicated that autophagy is a key factor in eliciting HTR-8/SVneo dysfunction after Ti3 C2 MXene exposure, which could therefore damage placental development. Autophagy inhibition is a potential therapeutic strategy for alleviating the placental toxicity of nanoparticles. Highlights: Ti3 C2 MXene can reduce the extension ability of human villus explants. Ti3 C2 MXene inhibits cell migration and invasion abilities. Cell ultrastructure, viability, and autophagy can be affected by Ti3 C2 MXene. Ti3 C2 MXene elevates cell autophagy by inhibiting PI3K/AKT/mTOR signaling pathway. An autophagy inhibitor (3-MA) reversed the effects of Ti3 C2 MXene in human trophoblasts.